Toxicity of surface-modified copper oxide nanoparticles in a mouse macrophage cell line: Interplay of particles, surface coating and particle dissolution. (April 2018) - Líbalová, Helena; Costa, Pedro M.; Olsson, Magnus; Farcal, Lucian; Ortelli, Simona; Blosi, Magda; Topinka, Jan; Costa, Anna L.; Fadeel, Bengt
Abstract: The rapid dissolution of copper oxide (CuO) nanoparticles (NPs) with release of ions is thought to be one of the main factors modulating their toxicity. Here we assessed the cytotoxicity of a panel of CuO NPs (12 nm ± 4 nm) with different surface modifications, i.e., anionic sodium citrate (CIT) and sodium ascorbate (ASC), neutral polyvinylpyrrolidone (PVP), and cationic polyethylenimine (PEI), versus the pristine (uncoated) NPs, using a murine macrophage cell line (RAW264.7). Cytotoxicity, reactive oxygen species (ROS) production, and cellular uptake were assessed. The cytotoxicity results were analyzed by the benchmark dose (BMD) method and the NPs were ranked based on BMD20 values. The PEI-coated NPs were found to be the most cytotoxic. Despite the different properties of the coating agents, NP dissolution in cell medium was only marginally affected by surface modification. Furthermore, CuCl2 (used as an ion control) elicited significantly less cytotoxicity when compared to the CuO NPs. We also observed that the antioxidant, N-acetylcysteine, failed to protect against the cytotoxicity of the uncoated CuO NPs. Indeed, the toxicity of the surface-modified CuO NPs was not directly linked to particle dissolution and subsequent Cu burden in cells, nor to cellular ROS production, although CuO-ASC NPs, which were found to be the least cytotoxic, yielded lower levels of ROS in comparison to pristine NPs. Hierarchical cluster analysis suggested, instead, that the toxicity in the current in vitro model could be explained by synergistic interactions between the NPs, their dissolution, and the toxicity of the coating agents. Graphical abstract: Image 1 Highlights: CuO nanoparticles (NPs) were cytotoxic for RAW264.7 macrophages. Surface modification altered the cytotoxicity of the CuO NPs. Particle dissolution or ROS production failed to explain the cytotoxicity. The coating agents themselves also contributed to the overall cytotoxicity.